Manajemen Stres Dan Ansietas Warga Di Kelurahan Bencongan Indah Tangerang - Maria Veronika Ayu Florensa; Veronica Paula; Yenni Sitanggang; Shinta Yuliana Hasibuan; Mega Tri Anggraini; Adventina Situngkir (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Mental health is a condition which person can develop physically, mentally, spiritually and social, and also able to contribute to his community. Individuals cannot be free from stress. If the stress not managed properly it can continue to become anxiety and other mental health problems. The 2018 Riskesdas data showed an increase in the number of psychosis sufferers from 1.7% to 7% per mile, increasing number also happened in depression suffers from 6 to 9% per mile. The number of depressed patients in Banten province reaches 8.7%. The high number of people with mental disorders from time to time requires action to promote and prevent mental disorders. The aims of this community service is to help people to understand the signs and symptoms of stress and anxiety and be able to practice the stress and anxiety management. The results of the activity were measured by comparing the score of the pre-test and post-test of the patient's knowledge before and after the administration of the material. As a result, there is an increase in people's knowledge regarding health, mental health, signs of symptoms of stress and anxiety. People are also able to practice the actions to manage stress and anxiety. This activity is expected to be carried out sustainably with the help of community cadres.